صورة المتمرد ودلالاتها في رواية الديوان الاسبرطي لعبد الوهاب عيساوي - بادة، سعدية, هالم، سيرين; صوالح محمد، هادية (University of El-oued, 2022)
انفتحت رواية ”الدّيوان الإسبرطيّ” لعبد الوهّاب عيساويّ على دراسات عدّة، ونخصّ بالذّكر دراسة الشّخصيّات الخمس البطلة (ديبون، كافيار، ابن ميّار، حمّة السّلاويّ، دوجة)، التي كانت محور الرّواية في فصولها الخمسة. حيث جاءت هذه الدّراسة الموسومة بــــ "صورة المتمرّد ودلالاتها في رواية الدّيوان الإسبرطيّ لعبد الوهّاب عيساويّ" للإحاطة بالمواصفات المختلفة للشّخصيّة المتمرّدة. وحتّى نصل إلى صورة التّمرّد تتّبعنا الشّخصيّات ووقفنا على دلالات كلّ شخصيّة، من ذلك: (المتّمرّد الثّوريّ، المعارض، الكادح، الغاضب، المنتقم، والمتّمرّد المسالم، المحاور، الرافض)، وجاءت الشّخصيّات الخمس بين المتفق والمختلف، وكوّنت صورة للتّمرد. فكان كافيار وحمّة السّلاويّ يمثّلان التّمرّد الحربيّ أو الكفاح المسلّح؛ من خلال الإيمان التّامّ بضرورة الثّورة والتّغيير، وأنّ ما أُخذ بالقوّة لا يستردّ إلاّ بالقوّة وذلك عن طريق حمل السّلاح والانضمام إلى صفوف الثّوّار أو المقاتلين كما فعل السّلاّويّ، أو عن طريق تحضير قوّة عسكريّة ضخمة استعدادا لإراقة الكثير من الدّماء على الجبهة الثّانية كما فعل كافيار. أمّا ديبون وابن ميّار فكانا يمثّلان صورة التّمرّد السّلميّ أو الكفاح السّياسيّ؛ الّذي يقوم على الإيمان التّامّ بضرورة التّغيير بطرق سلميّة سياسيّة بحتة؛ عن طريق الحوار السّلميّ وتقديم العرائض أو الشّكاوى التي تلخّص مطالب الشّعب دون اللّجوء إلى حمل السّلاح. رغم الاختلاف الشّديد للشّخصيّات إلّا أنّه ثمّت اتفاق واحد؛ هو دوجة الّتي كانت تمثّل صورة الجزائر في كلّ أحوالها، إذ كانت كلّ شخصيّة ترغب في تملّكها، لكن كلّ حسب طريقته. The novel "The Spartan Court" by Abd al-Wahhab al-Issawi was opened to several studies, and we single out It is worth mentioning the study of the five heroic characters (Dibon, Caviar, Ibn Mayar, Hama Al-Salawi, Doja), Which was the focus of the novel in its five chapters. Where this study came tagged with the image of the rebel and its connotations in the novel Al-Diwan The Spartan by Abdel Wahab Issawi" to capture the different specifications of the arrogant personality. In order to reach the image of the rebellion, we saturated the characters and stood on the connotations of each character, from That is: (the revolutionary rebel, the opposition, the industrious, the angry, the avenger, the peaceful rebel, the interlocutor, The rejectionist), and the five personalities came between those who agreed and disagreed, and formed a picture of the thirred. Caviar and Hamma al-Shalawi represented war rebellion or armed struggle; through The supreme belief in the necessity of revolution and change, and that what was taken by force can only be recovered by force, and that is through Take up arms and join the ranks of the revolutionaries or fighters, as Al-Salawi did, or by Prepare a huge military force in preparation for spilling a lot of blood on the second front as he did A Caviar. As for Dibon and Ibn Mayar, they represented the image of peaceful rebellion or political struggle; that It is based on the fundamental belief in the necessity of change by peaceful and purely political means; through dialogue Peacefully and submitting petitions or complaints that summarize the people’s demands without resorting to pregnancy weapon. Despite the very different personalities, there is one agreement; He is a doge that was representing The image of Algeria in all its circumstances, as every character wanted to own it, but each according to her his way.
Keywords: الشّعب، تقديم العرائض، دي بورمون، المُستَعمَر الفرنسيّ، المتمرّد السّلميّ، المتمرّد الثّوريّ.; the revolutionary rebel, the peaceful rebel, submitting complaints, the people’s, french colonizer, De Bourmont.